Madagascar Digital Economy Assessment - World Bank (Washington, DC, 2022)
Madagascar is an island nation located in the Indian Ocean off the south-eastern coast of Africa, and the fourth-largest island in the world. Despite the country’s extensive economic opportunities and expansive natural resources, real GDP per capita is one of the lowest in the world. This situation can largely be imparted to decades of political instability and recurring crises, which have severely thwarted development efforts. The time is opportune to leverage the potential of digital technology to support a responsive government and promote a vibrant digital economy. Digital transformation has been described as the fourth industrial revolution, and if harnessed strategically, it can help reduce inequalities, and promote economic growth and high value job creation. It can also improve access to public services and to information, thereby strengthening government accountability and trust in the State. Much remains to be done in Madagascar. Madagascar has already made remarkable progress in the digital economy. Preparation of this diagnostic involved desk research on the areas comprising the five digital economy pillars, as well as several in-country missions during which members of a core research team conducted broad consultations with counterparts, government, the private sector, and user representatives.